Chemotoxicity of doxorubicin and surface expression of P-glycoprotein (MDR1) is regulated by the Pseudomonas aeruginosa toxin Cif - Ye, Siying (American Physiological Society, 2008)
P-glycoprotein (Pgp), a member of the adenosine triphosphate-binding cassette (ABC) transporter superfamily, is a major drug efflux pump expressed in normal tissues, and is overexpressed in many human cancers. Overexpression of Pgp results in reduced intracellular drug concentration and cytotoxicity of chemotherapeutic drugs and is thought to contribute to multidrug resistance of cancer cells. The involvement of Pgp in clinical drug resistance has led to a search for molecules that block Pgp transporter activity to improve the efficacy and pharmacokinetics of therapeutic agents. We have recently identified and characterized a secreted toxin from Pseudomonas aeruginosa, designated cystic fibrosis transmembrane conductance regulator (CFTR) inhibitory factor (Cif). Cif reduces the apical membrane abundance of CFTR, also an ABC transporter, and inhibits the CFTR-mediated chloride ion secretion by human airway and kidney epithelial cells. We report presently that Cif also inhibits the apical membrane abundance of Pgp in kidney, airway, and intestinal epithelial cells but has no effect on plasma membrane abundance of multidrug resistance protein 1 or 2. Cif increased the drug sensitivity to doxorubicin in kidney cells expressing Pgp by 10-fold and increased the cellular accumulation of daunorubicin by 2-fold. Thus our studies show that Cif increases the sensitivity of Pgp-overexpressing cells to doxorubicin, consistent with the hypothesis that Cif affects Pgp functional expression. These results suggest that Cif may be useful to develop a new class of specific inhibitors of Pgp aimed at increasing the sensitivity of tumors to chemotherapeutic drugs, and at improving the bioavailability of Pgp transport substrates.